Gambaran Diagnostik Dan Penatalaksanaan Pasien Penyakit Paru Obstruksi Kronik - Balraj Kaur; Rudolf S. Parhusip; Puji Pinta O. Sinurat (Universitas Methodist Indonesia, 2024)
Background: World Health Organization (WHO), Indicate in 1990 occupy 6th order as the leading cause of death and will occupy 3rd order after cardiovascular disease and cancer.In Indonesia estimated 4,8 million patients with prevalence 5,6%. Method: This research was conducted by using descriptive research design with cross sectionall approach. The number of samples is 80 people withsimple random sampling technique. Results: Based on the result of research from 80 samples of patients obtained most age ≥60 years ie 50 patients (62,5%),the most of gender is male 69 patient (86,3%),the most of clinical symptoms is shortness of breath 42 patient (52,5%),the most of smokers status is active smoker 58 patient (72,5%), the most of job is entrepreneur 30 patient (37,5%),the most of examination support is radiology 50 patient (62,5%), the most of management is bronchodilator 35 patient (43,7%) and the most of mortality rate was in the ICU room 5 patient (50%). Conclusion: The result showed with Chronic Obstructive Pulmonal Disease the most treated was male patiens with age ≥65 years, the most of job is entrepreneur, which have a history of smoking with clinical symptoms of shortness breath and cough phlegm, the most of used examintaion support is radiology and the most of management is bronchodilator. Choronic Obstructve Pulmonal Disease management is excellent with fewer deaths.